Trialling The Sensemaker Methodology To Conceptualise Precarious Work Among Employed Individuals In South Africa - Strydom, Camille (Organisational Psychology, 2024)
Although precarious work is not a new phenomenon, birthed out of the development of paid employment in the 19th century (Kalleberg, 2009), a steady rise in precarious working arrangements has become cause for concern, due to its many adverse consequences. The aim of this dissertation is to evaluate whether The Work Precarity Framework and the Psychology of Working Theory reflect the experiences of precarious workers in South Africa. This study used the SenseMaker tool to collect data and the SenseMaker methodology to guide the research process. Data was collected by 15 data capturers after they had been trained in how to use the data collection tool. A total of 204 working individuals residing in Khayelitsha and Mitchells Plain in Cape Town narrated a story related to the question: “Tell me a story about your work which made you feel really bad or really good.” and interpreted their narrative on dimensions presented to them. Results indicate that experiences associated with precarious work are closely related to poor working conditions which manifest in feelings of anger, resentment, poor well-being and reduced satisfaction and commitment to their jobs. Other consequences include feelings of marginalization, including discrimination and inequality. The results of this study therefore indicate the importance of limiting exposure to precarious working conditions to improve people's lives at work and outside of work because of the deeply interwoven relationship between life and work. Contextual factors, such as the ability to meet basic survival needs, such as taking care of their families, influence whether participants are able to cope with precarious working conditions. Although the results from this study show that the Work Precarity Framework and Psychology of Working Theory capture a significant number of experiences of precarity in South Africa, specific contextual factors including positive attitudes and behavioural outcomes despite precarity are not adequately captured by the theories. These theories can therefore be said to lack the cultural and contextual nuances which would enable them to adequately account for all experiences of precarious work in South Africa.